2020
DOI: 10.1002/lsm.23367
|View full text |Cite
|
Sign up to set email alerts
|

OCT‐Based Angiography and Surface Topography in Burn‐Damaged Skin

Abstract: Background and Objectives There is a clinical need for an accurate, non‐invasive imaging tool that can provide the objective assessment of burn wounds. The aims of this study are to demonstrate the potential of optical coherence tomography (OCT) in evaluating burn wound healing, as well as exploring the physiological basis of human wound healing. Study Design/Materials and Methods This was a retrospective study. Seven patients with severe burn wounds who were admitted to Harborview Medical Center were imaged u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…With the gradual popularization of OCTA applications, their application value in various fields of medicine has been increasingly reflected. 19,32,33 Using OCTA techniques, this study provides an overview of changes in vascular and structural characteristics during skin healing at a spatiotemporal level. In this study, it was observed that the gelling agent could significantly promote angiogenesis on the wound surface of full-thickness skin defects in Wistar rats, mainly by significantly increasing the diameter, density, and circumference of blood vessels, indicating that PDGF had a significant effect on the improvement of wound microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…With the gradual popularization of OCTA applications, their application value in various fields of medicine has been increasingly reflected. 19,32,33 Using OCTA techniques, this study provides an overview of changes in vascular and structural characteristics during skin healing at a spatiotemporal level. In this study, it was observed that the gelling agent could significantly promote angiogenesis on the wound surface of full-thickness skin defects in Wistar rats, mainly by significantly increasing the diameter, density, and circumference of blood vessels, indicating that PDGF had a significant effect on the improvement of wound microcirculation.…”
Section: Discussionmentioning
confidence: 99%
“…The wound should be rinsed with a sufficient quantity of fluid and a certain impact to achieve a better effect. However, wounds need adequate hemostasis before pulsed lavage to prevent blood coagulation or damage to the exposed nerve endings [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…OCT scanning was performed using an in-house-built swept-source OCT (SS-OCT) system with a central wavelength of 1310 nm, and a bandwidth of 100 nm. More detailed system information is available in our previous publications [15,16,43]. The handheld probe was specifically designed with a sample spacer to keep the skin at a fixed distance from the objective lens.…”
Section: Oct Imagingmentioning
confidence: 99%
“…Another promising form of OCT is OCT-based angiography (OCTA), which is a functional extension of OCT that can provide vascular information without the need for invasive contrast agents. A number of studies, such as those conducted by Deegan et al [13][14][15] and Lu et al [16], have demonstrated the potential of OCTA to both qualitatively and quantitatively assess the vascular response to burn injury over time. Despite the increased applicability of OCT in its various forms, however, studies regarding the visualization and subsequent measuring of epidermal thickness in skin post-injury are limited.…”
Section: Introductionmentioning
confidence: 99%